2023
DOI: 10.1111/opo.13186
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dry eye disease on corneal nerve parameters: A systematic review and meta‐analysis

Abstract: PurposeDry eye disease (DED) is a growing global health problem with a significant impact on the quality of life of patients. While neurosensory abnormalities have been recognised as a contributor to DED pathophysiology, the potential role of in vivo corneal confocal microscopy in detecting nerve loss or damage remains unclear. This systematic review with meta‐analysis (PROSPERO registered CRD42022381861) investigated whether DED has an impact on sub‐basal corneal nerve parameters.MethodsPubMed, Embase and Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(396 reference statements)
0
1
1
Order By: Relevance
“…In their next study [90], the same algorithm measured sub-basal nerve parameters to investigate the association between oval cells, Langerhans cells (LCs), and dry eye disease. In opposition to the studies [91,92] showing a decrease in the nerve length, it was observed that-with the presence of the LCs and bright, oval cells-there was a greater corneal peripheral nerve maximum length and average density. This suggests that the changes in corneal nerve density and nerve number are related to the level of advancement of the dry eye disease.…”
Section: Dry Eye Diseasecontrasting
confidence: 84%
See 1 more Smart Citation
“…In their next study [90], the same algorithm measured sub-basal nerve parameters to investigate the association between oval cells, Langerhans cells (LCs), and dry eye disease. In opposition to the studies [91,92] showing a decrease in the nerve length, it was observed that-with the presence of the LCs and bright, oval cells-there was a greater corneal peripheral nerve maximum length and average density. This suggests that the changes in corneal nerve density and nerve number are related to the level of advancement of the dry eye disease.…”
Section: Dry Eye Diseasecontrasting
confidence: 84%
“…In their next study [90], the same algorithm measured subbasal nerve parameters to investigate the association between oval cells, Langerhans cells (LCs), and dry eye disease. In opposition to the studies [91,92] showing a decrease in the Shanshan Wei et al [88] designed a deep learning model called CNS-Net, which was designed to analyze sub-basal nerve morphologies. It allowed for the possibility of obtaining the average density and the maximum length of the nerve fiber with a high accuracy that produced an AUC of 96%.…”
Section: Dry Eye Diseasementioning
confidence: 99%